Evaluation of Energy-efficiency in Lighting Systems for Public Buildings - Oluseyi, Peter Olabisi; Somefun, Tobiloba Emmanuel; Babatunde, Olubayo Moses; Akinbulire, Tolulope Olusegun; Babayomi, Oluleke O.; Isaac, Samuel A.; Babatunde, Damilola Elizabeth (International Journal of Energy Economics and Policy, 2020)
Adoption of energy efficiency and conservation techniques in public buildings in Nigeria is significantly low due to the ignorance of its potential benefits. Consequently, this study presents the prospects of energy saving using different methods in a public building at a Nigerian University. A proposed remodelled students' residential hostel at the University of Lagos, Nigeria was chosen as a pilot study. This research utilized three energy efficient lighting technology alternatives namely; intelligent controlled Incandescent lamp (ICIL), compact fluorescent lamp (CFL), and intelligent controlled CFL (ICCFL) and compared with a base case of conventional incandescent lighting configuration. Energy consumption, at the proposed hostel is analysed and modelled. The effectiveness of each lighting technology alternative and base case in terms of cost is estimated using economic indices such as the net present value (NPV), savings to investment ratio (SIR) and the discounted payback period (DPP). Results show that the CFL lighting technology give 39% cost benefit as compared to ICCFL which gives 11% overall cost benefit. From the study, it is established that adoption of energy efficient lighting techniques save a significant amount of energy, operational cost, electricity bills and consequently reduce emission. Keywords: Energy saving, Net present value, Savings to investment ratio, discounted payback period JEL Classifications: C63, Q48 DOI: https://doi.org/10.32479/ijeep.9905